Microbial contributions to maize crop production: a comprehensive review of challenges and future perspectives - Nazia Baloch (Discover Agriculture)
Abstract Ensuring a stable supply of nutritious food for the growing global population is a major challenge, especially through a sustainable food system. Maize is host to a vast microbial community in its root zone. Microorganisms associated with maize play an essential role in enhancing plant growth and productivity. The purpose of this review is to explore the interactions within the rhizosphere of maize, focusing on plant growth-promoting rhizobacteria (PGPR), contribute to improved phosphorus solubilization, nitrogen fixation, and overall plant health. Through the synthesis of 200 papers, elucidated the interactions within the maize rhizosphere, highlighting the activity and assembly mechanisms of soil microorganisms crucial to maize crop production that have been widely analyzed. Incorporating microbial benefits into sustainable agricultural practices presents several challenges, including environmental variability (temperate vs tropical), unpredictable field performance, and the influence of advanced crop management techniques on microbial communities. To address these challenges, future research should prioritize microbiome engineering, precision agriculture, and the development of climate-resilient microbial strains. A deeper understanding of the maize microbiome holds significant potential for advancing biofertilizer development and sustainable farming practices by overcoming technological, environmental large-scale implementation.